The Genesis of APEC: Economic Diplomacy of Australia, Japan, and the United States (On the 30th Anniversary of the Forum) - A. A. Sidorov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In 2019 the Asia-Pacific Economic Cooperation forum (APEC) celebrates its 30th anniversary. APEC emerged at a turning point in international relations history as the break-up of the socialist camp ruled out the alternative to capitalism model of social and political development and created new opportunities for internationalization of production. However, those new opportunities were yet to be realized. The 30th anniversary of APEC provides a good opportunity to revisit the history of the forum and to highlight complex negotiations between the countries of the Asia-Pacific region at the end of the Cold War. The paper examines both the structural factors that shaped global and regional contexts of the negotiation process and the role of those politicians and diplomats who had decisively contributed to the success of the negotiations. Special focus is made on the role of the United States, Australia, and Japan. The author examines their views on a wide range of issues related to the development of economic and political cooperation in the Asia-Pacific region, including its aims and scope, institutional arrangements, potential participants, and prospects for cooperation with regional organizations (the Association of Southeast Asian Nations (ASEAN) — in particular) and mechanisms of global trade management (primarily — the General Agreement on Tariffs and Trade (GATT)). As for the ASEAN member states, the author emphasizes that they were particularly concerned that a new forum would place itself centrally in the regional economic cooperation and would overshadow the Association. In addition, they sought to ensure that APEC won’t be dominated by larger, stronger states, notably by the United States and Japan. Under these conditions, Australia decided to take the initiative. It managed to dispel major fears of the ASEAN member states and convinced them to join the new regional alliance, and ultimately it was Australia who played the central role in founding of APEC. At the same time the author notes that the forum has gone far beyond the initial expectations of its creators: it is not merely an effective tool for further trade liberalization in the Asia-Pacific region, but a unique platform for consultation, negotiation, and decision-making process suited for needs and capacities of each individual member state. As a result, economic cooperation among countries of the Pacific has reached a fundamentally new level.